(untitled) (Bangladesh Journal of Zoology, 2024)
Hitherto the authors reported, a total of 3 genera viz: Amrasca Ghauri, 1967; Distantasca Dworakowska 1972; Empoasca Walsh, 1862 under the tribe Empoascini Distant, 1908 (Cicadellidae: Typhlocybinae) have been known to be reported in Bangladesh. In the course of the taxonomic survey on the empoascine leafhoppers from Bangladesh, we recorded another genus for the first time Apheliona Kirkaldy, 1907. The constituent species Apheliona ferruginea (Matsumura, 1931), is included in the faunal checklist of Bangladesh. Diagnostic descriptions, illustrations discriminating species and a revised checklist as well as the key to the genera under the tribe Empoascini from Bangladesh are also provided here. Bangladesh J. Zool. 52(1): 111-118, 2024